Interstitial Ectopic Pregnancy with Enhanced Myometrial Vascularity: A Rare Case Successfully Treated with Uterine Artery Embolization - Khurana, Navpreet Kaur; Gangwani, Gaurav; Thiyagarajan, Kamalapriya; Chaurasia, Aditi; Thakre, Akanksha (Journal of Clinical Interventional Radiology ISVIR, 2023)
Enhanced myometrial vascularity (EMV) is a rare disorder associated with various obstetrical and gynecological pathologies. We describe a unique case of interstitial ectopic pregnancy associated with EMV successfully managed with bilateral uterine artery embolization.
Keywords: uterine artery embolization; enhanced myometrial vascularity; ectopic pregnancy